Divisionalization in vertical structures. - Bru, Lluís; Fauli-Oller, Ramon; Ordóñez-de-Haro, José Manuel (Wiley, 2024)
We evaluate the incentives to create within-industry independent divisions once thevertical structure of the industry is considered. Divisionalization allows a firm to gainmarket share in the final market, but it also leads to an increase in total payments tothe input supplier. The less competitive the upstream market, the more important thesecond effect will be, and this reduces the profitability of divisionalization. As aconsequence, a less competitive upstream segment leads to a lower total number ofdivisions in equilibrium and a less competitive final market, harming end consumerswho will face higher prices.
Keywords: Mercado - Análisis; Industria - Aspectos económicos; Análisis coste-beneficio; Economía aplicada; Organizational design; Rivalry; Intermediate markets; Divisionalization